ANALISIS KEBUTUHAN PEMBELAJARAN BERBASIS RAPOR PENDIDIKAN 2025 UNTUK PENGUATAN KOMPETENSI INOVASI GURU SMP DI PROVINSI BANTEN - Setiawati, Dewi; Abdullah Abdullah; Hari Wibowo; M. Isnaini; Endang Setyorini; Dwi Cahyo Widodo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to analyze the learning needs based on the 2025 Education Report Card to strengthen teachers' innovation competencies in a more targeted and evidence-based manner. The methodology used is a quantitative descriptive approach through a documentation study of the 2025 Education Report data covering 1,657 junior high schools in Banten Province. The data was analyzed using gap analysis techniques by referring to the Teacher Competency Model in accordance with national regulations. The analysis process includes identifying quality indicators, mapping competency needs, and determining intervention priorities. The results showed that as many as 823 schools (49.67%) were in the low achievement category and experienced declines in various indicators, especially in the aspects of literacy (A1), numeracy (A2), innovative learning practices (D2), and education quality financing support (E2). Tangerang Regency is the area with the highest level of need in almost all indicators. These findings indicate the need to strengthen teachers' innovation competencies that focus on technology integration, learning data processing, authentic evaluation, and continuous reflection. Thus, the results of this research can be the basis for designing a more adaptive, contextual, and data-based Continuous Professional Development (CPD) program to improve the quality of education in Banten Province